PEER ASSESSMENT OF SOCIAL BEHAVIOUR AN GENDER IN ADOLESCENCE - Muñoz Tinoco, María Victoria; Jiménez Lagares, Irene; Moreno Rodríguez, Mª Carmen (Anales de Psicología / Annals of Psychology, 2008)
This works is part of a study of adolescent social relationships wich used a multi-method perspective with reports from different agents (teachers, peers and adolescents themselves), we studied the assessment of social behavor by peers using an adapted version of the Revised Class Play (Masten, Morison, y Pellegrini, 1985) with a sample of 1009 adolescents (514 boys and 495 girls) of Seville. Differences were found between boys and girls in most of the items, and also un the factors obtained through a confirmatory factorial analysis of the content of the scale (sociability, aggression-disruption, annoyance an isolation). Girls had higher average in sociability, and boys in aggression and annoyance. Isolation, however, didn’t show gender differences.